Toxicity studies of octahydro-tetramethyl-naphthalenyl-ethanone (OTNE) administered dermally to F344/NTac rats and B6C3F1/N mice. (Toxic Rep Ser, 2016)
Octahydro-tetramethyl-naphthalenyl-ethanone (OTNE) is a fragrance ingredient that is formed as a mixture of isomers with a basic unsaturated alkyl cyclic ketone structure. The main isomer is 1-(1,2,3,4,5,6,7,8-octahydro-2,3,8,8-tetramethyl-2-naphthalenyl)ethanone (β-isomer). Two other predominant isomers within the mixture are 1-(1,2,3,4,6,7,8,8a-octahydro-2,3,8,8-tetramethyl-2-naphthalenyl)ethanone (α-isomer) and 1-(1,2,3,5,6,7,8,8a-octahydro-2,3,8,8-tetramethyl-2-naphthalenyl)ethanone (γ-isomer). OTNE is used as a perfume ingredient in soap, shampoo, cologne, liquid detergent compounds, and malodor-reducing compounds. Male and female F344/NTac rats and B6C3F1/N mice were administered OTNE (greater than 92.3% pure with respect to the 3 prominent isomers) dermally for 3 months. Genetic toxicology studies were conducted in Salmonella typhimurium, Escherichia coli, and rat and mouse peripheral blood erythrocytes. (Abstract Abridged).